2017
DOI: 10.1002/ccr3.1087
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular large B‐cell lymphoma presenting as Richter's syndrome with cerebral involvement in a patient with chronic lymphocytic leukemia

Abstract: Key Clinical MessageIntravascular large B‐cell lymphoma (IVLBCL) is an aggressive non‐Hodgkin's lymphoma which can present with B symptoms, rash, and neurological deterioration. Up to 10% of cases of IVLBCL are associated with other hematological neoplasms, including this extremely rare presentation of IVLBCL as Richter's transformation in chronic lymphocytic leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In general, larger blood vessels are not involved, although cases have been reported that showed involvement as a tumour thrombus or a mass attached to large vessel walls. 31 Emergence of IVLBCL following small B-cell lymphoma or diffuse large B-cell lymphoma has been reported; 32,33 whether these cases represent transformation or de novo disease is not clear and these cases are not further discussed here.…”
Section: Definitionmentioning
confidence: 99%
“…In general, larger blood vessels are not involved, although cases have been reported that showed involvement as a tumour thrombus or a mass attached to large vessel walls. 31 Emergence of IVLBCL following small B-cell lymphoma or diffuse large B-cell lymphoma has been reported; 32,33 whether these cases represent transformation or de novo disease is not clear and these cases are not further discussed here.…”
Section: Definitionmentioning
confidence: 99%